Border controls in transit countries and their implications for migrant smuggling: a comparison of Indonesia and Mexico - Galemba, Rebecca Berke (Smuggling of migrants, 2019)
Indonesia and Mexico are both considered transit countries for irregular migrants, including potential asylum seekers and even recognized refugees heading to potential destination countries such as Australia and the United States of America. Because their geographic location places them strategically close to the land or sea border of potential destination countries, Indonesia and Mexico have made attempts to develop externalized border protection. They have also been pressured to strengthen their borders, migration policies and anti-smuggling legislation so that they can serve as bulwarks against unwanted migrants and smugglers. Although the causes and conditions of irregular migration in Indonesia and Mexico and differ, a comparison of how these two transit countries have adjusted to political pressure to deter undesired migrants and prevent smuggling allows for an interregional assessment of how extraterritorial border policies materialize in transit countries. A comparative assessment demonstrates how such policies have caused smuggling practices on the ground to shift and illustrates differences and similarities between land and sea borders.